Myocardial extracellular volume is a non-invasive tissue marker of heart failure in patients with transposition of the great arteries and systemic right ventricle - Al-Wakeel-Marquard, Nadya; Ferreira da Silva, Tiago; Berger, Felix; Kuehne, Titus; Messroghli, Daniel R. (Frontiers in Pediatrics, 2022)
Background Focal myocardial fibrosis in the systemic right ventricle (RV) is related to ventricular dysfunction and adverse outcome in patients with d-transposition of the great arteries (dTGA) post atrial redirection and those with congenitally corrected TGA (ccTGA). The role of diffuse fibrotic lesions in these conditions remains poorly understood. Our study aimed to investigate diffuse myocardial fibrosis by measuring extracellular volume (ECV) with cardiovascular magnetic resonance (CMR) and to explore correlations between ECV and clinical as well as functional markers of heart failure in patients with TGA and systemic RV. Methods We prospectively included dTGA and ccTGA patients aged ≥14 years and compared them to healthy controls. Standardized CMR included modified Look-Locker Inversion recovery T1 mapping to quantify diffuse myocardial fibrosis in the systemic RV and the subpulmonary left ventricle (LV). The centerline of RV and LV myocardium was marked with a line of interest tool to determine native and post-contrast T1 for quantification of ECV. Results In total, 13 patients (dTGA: n = 8, ccTGA: n = 5) with a median age of 30.3 years were enrolled. LV ECV was higher in patients than in controls [34% (30%–41%) vs. 26% (23%–27%), p < 0.001], with values increased above the upper limit of normal in 10/13 patients (77%). RV ECV tended to be higher in patients than in controls, albeit without statistical significance [29% (27%–32%) vs. 28% (26%–29%), p = 0.316]. Patients with elevated LV ECV had lower LV ejection fraction than those with normal ECV (52 ± 5% vs. 65 ± 4%, p = 0.007). Correlations with clinical parameters were not observed. LV ECV was significantly higher than RV ECV (p = 0.016) in the patient group. Conclusions In this study, LV ECV was significantly increased in TGA patients compared to controls, and was associated with LV dysfunction. Our data suggest that ECV may serve as a non-invasive tissue marker of heart failure in TGA with systemic RV. Further research is necessary to evaluate the prognostic implications and the potential role of ECV in monitoring disease progression and guiding therapy, aiming to maintain LV function or train the LV for subaortic location in TGA patients from infancy to adulthood.